Pengaruh Konfigurasi Sudut Chamfer Male-Female dan Lama Gesek Terhadap Karakteristik Hasil Pengelasan dan Kekuatan Tarik Paduan Alumunium 6061 - Kasijanto Kasijanto; Sadar Wahjudi; Listiono Listiono (Jurnal Energi dan Teknologi Manufaktur, 2018)
This study aims to analyzed the effect of male-female chamfer configuration in a rotary friction welding of alumunium 6061. The male-female chamfer configuration tend to make an inner chamfer and outer chamfer shape between two connected materials. The chamfer angle analyzed varies in 300, 450, and 600 where the friction time also varies in 1 and 2 minute. The results shows that the tensile strength increased along with smaller chamfer angle and longer friction time. The largest tensile strength of 33.92 kgf / mm2 was obtained in the variation B30. The smallest tensile strength of 12.20 kgf/mm2 gained in specimen A60. Smaller chamfer angle leads to a larger friction areas which caused the welding contact areas also wider. The male-female chamfer method slopely increase the contact area by 78%, 33% and 12% than normal circle profile.